Titanium-molybdenum-zirconium pre-alloyed powder, method for preparing same, dental restoration and method for preparing same

By preparing titanium-molybdenum-zirconium pre-alloy powder with Mo: 12%~20% and Zr: 4%~10%, and combining it with SLM process and two-step heat treatment, the issues of biocompatibility and porcelain compatibility of titanium alloy powder used in SLM were solved, and the stable performance of dental restorations was achieved.

CN123043371APending Publication Date: 2026-11-06NANJING CHAMLION LASER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611365651.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

The existing titanium alloy powder used for SLM has biosafety risks related to Al and V elements and insufficient ceramic matching, making it difficult to simultaneously meet the performance requirements of ceramic crown bridge metal substrate and removable bracket with clasp. Furthermore, its performance degrades after multiple ceramic thermal cycles.

Method used

A titanium-molybdenum-zirconium pre-alloy powder was developed with the following chemical composition: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%. It was prepared by aerosol method and subjected to controlled oxidation treatment. Combined with SLM process and two-step heat treatment, a dental restoration with good strength, plasticity and elastic modulus matching was prepared.

Benefits of technology

It eliminates the biosafety risks associated with Al and V elements, achieves performance matching of the same material in both ceramic crown metal substrates and removable scaffolds with retainers, and maintains tissue and performance stability after multiple ceramic thermal cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123043371A_ABST
    Figure CN123043371A_ABST
Patent Text Reader

Abstract

This invention relates to a titanium-molybdenum-zirconium pre-alloy powder and its preparation method, as well as dental restorations and their preparation methods, belonging to the field of biomedical metallic materials technology. The titanium-molybdenum-zirconium pre-alloy powder, by mass percentage, comprises: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%, with the balance being Ti and unavoidable impurities. The titanium-molybdenum-zirconium pre-alloy powder provided by this invention does not contain Al or V elements, thus eliminating the biosafety risks associated with Al and V elements. It also allows the same material to meet both the strength and ceramic bonding requirements of the metal substrate for porcelain-fused-to-metal crowns and bridges, and the resilience and plasticity requirements of removable support structures with clasps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical metallic materials technology, specifically to a titanium-molybdenum-zirconium pre-alloy powder and its preparation method, and a dental restoration and its preparation method. Background Technology

[0002] Selective laser melting (SLM) technology provides an effective approach for the customized and precision manufacturing of dental restorations. SLM technology uses a laser beam as an energy source to scan and melt metal powder layer by layer according to the contour of a three-dimensional model slice. This allows for the direct forming of dental restorations with complex internal cavities, thin walls, and delicate clasp structures, significantly improving forming accuracy and material utilization compared to traditional casting processes.

[0003] However, the forming quality of SLM technology is highly dependent on the performance of the metal powder. Currently, the titanium alloy powder used in SLM is mainly concentrated in Ti-6Al-4V (TC4). However, the vanadium (V) contained in TC4 may cause concerns about biological effects when released from dental implants. At the same time, although the release of Al / V in TC4 is small, long-term exposure still poses a risk of cell and tissue toxicity, which can lead to complications such as organ damage, osteomalacia, anemia, and neurological disorders. Therefore, restorations formed using TC4 also have the above-mentioned problems caused by the presence of Al and V elements in TC4. As for the titanium-molybdenum-zirconium (Ti-Mo-Zr) pre-alloy powder developed for the specific conditions of dental restoration, which is Al / V-free and suitable for SLM process, a systematic technical solution has not yet been formed in terms of powder composition design, particle size and shape control, oxygen, nitrogen and hydrogen impurity control, and subsequent heat treatment. Summary of the Invention

[0004] Therefore, the purpose of this invention is to provide a titanium-molybdenum-zirconium pre-alloy powder and its preparation method, as well as a dental restoration and its preparation method, to eliminate the potential biosafety risks of Al and V elements in dental restorations.

[0005] The first aspect of the present invention provides a titanium-molybdenum-zirconium pre-alloyed powder, the chemical composition of which, by mass percentage, includes: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%, with the balance being Ti and unavoidable impurities.

[0006] Optionally, the titanium-molybdenum-zirconium pre-alloy powder is an alloy powder prepared by an aerosol method; the particle size distribution D10 of the titanium-molybdenum-zirconium pre-alloy powder is 12μm~25μm, the particle size distribution D90 is 50μm~65μm, and the sphericity of the titanium-molybdenum-zirconium pre-alloy powder is ≥0.85.

[0007] Optionally, the flowability of the titanium-molybdenum-zirconium pre-alloyed powder is ≤40s / 50g, and the loose pack density of the titanium-molybdenum-zirconium pre-alloyed powder is ≥2.8g / cm³. 3 .

[0008] Optionally, after the titanium-molybdenum-zirconium pre-alloyed powder undergoes one laser selective melting treatment, the increase in its oxygen content is ≤100ppm and its sphericity is ≥0.80.

[0009] Optionally, the surface of the titanium-molybdenum-zirconium pre-alloyed powder particles is formed with an oxygen enrichment gradient layer with a thickness of 50 nm to 500 nm. The oxygen content in the oxygen enrichment gradient layer decreases from the surface to the interior of the particles. The oxygen content at the surface of the oxygen enrichment gradient layer is ≥0.25 wt%, and the oxygen content at the core of the oxygen enrichment gradient layer is ≤0.10 wt%.

[0010] The titanium-molybdenum-zirconium pre-alloy powder provided by this invention does not contain Al or V elements and can solve the following three key technical problems: First, it eliminates the biosafety hazards of Al and V elements; second, it enables the same material to meet both the strength and ceramic bonding requirements of the metal substrate of porcelain crowns and bridges, and the resilience and plasticity requirements of removable stents with clasps; third, it ensures that the restoration can maintain tissue and performance stability after multiple porcelain heating cycles, thereby overcoming the inherent defects of "one material cannot be used for two purposes" and "performance decay after porcelain heating cycles" in the prior art.

[0011] A second aspect of the present invention provides a method for preparing the titanium-molybdenum-zirconium pre-alloyed powder as described above, comprising the following steps: (1) Prepare the raw materials for titanium-molybdenum-zirconium pre-alloyed to prepare electrode rods using the prepared raw materials; (2) The electrode rod prepared in step (1) is powdered under the protection of high-purity argon gas by using the electrode induction melting gas atomization method to obtain the titanium-molybdenum-zirconium pre-alloy powder.

[0012] Optionally, the process further includes: subjecting the formulation obtained in step (2) to controlled oxidation treatment for 1 to 4 hours at a temperature of 300°C to 500°C and an oxygen partial pressure of 0.001 atm to 0.1 atm, so that the surface layer of the formulation forms an oxygen-enriched gradient layer with a thickness of 50 nm to 500 nm, and controlling the overall oxygen content of the titanium-molybdenum-zirconium pre-alloy powder to 0.05 wt% to 0.20 wt%.

[0013] The method for preparing titanium-molybdenum-zirconium pre-alloyed powder provided by the present invention can fully fuse Mo and Zr elements by pre-mixing and forming rods, and then combining them with electrode induction melting. The resulting powder particles have good compositional consistency, reduce the performance dispersion of SLM formed components, and ensure "one material for two uses". At the same time, it is suitable for the performance requirements of porcelain crown bridge substrate and removable bracket with retaining ring.

[0014] A third aspect of the present invention provides a method for preparing a dental restoration, comprising the following steps: (1) Under the protection of an inert gas with an oxygen content ≤0.1%, the above-mentioned titanium-molybdenum-zirconium pre-alloy powder is spread to form a powder layer with a thickness of 20μm~40μm; (2) The powder layer formed in step (1) is laser selective melting and forming to obtain a matrix by using preset process parameters; the preset process parameters are: laser power of 90W~250W, scanning speed of 500mm / s~1200mm / s, and scanning distance of 45μm~110μm. (3) Using a combination of checkerboard scanning and rotation scanning, the scanning direction of adjacent layers is rotated by 67° to form the substrate obtained in step (2) to obtain a shaped part; (4) The molded part obtained in step (3) is subjected to two heat treatments and polishing treatments in sequence to obtain the dental restoration; wherein, the first heat treatment of the molded part includes holding it at a heat treatment temperature of 760℃~790℃ for 20min~60min and then air cooling it to room temperature; the second heat treatment of the molded part includes holding it at a heat treatment temperature of 660℃~790℃ for 1h~2h and then air cooling it to room temperature.

[0015] The fourth aspect of the present invention provides a dental prosthesis, which is prepared by the above-described method for preparing dental prostheses, wherein the prosthesis is a porcelain crown bridge with a metal base or a removable partial denture framework with clasps. Optionally, the relative density of the dental restoration is ≥99.5%, the microstructure is a β-phase matrix with diffusely distributed α-precipitates, and the volume fraction of the β-phase is ≥70%; the specified non-proportional elongation strength Rp0.2 of the dental restoration is 780MPa~950MPa, the elongation after fracture is ≥8%, and the elastic modulus is ≤105GPa; after three cycles of simulated porcelain fusion at 850℃, the Rp0.2 of the dental restoration remains at 780MPa~950MPa, the decrease in elongation after fracture is ≤20%, and the metal-ceramic bond strength is ≥30MPa.

[0016] The dental restorations prepared by this invention can eliminate the biosafety risks of Al and V elements, and since Mo and Zr are both recognized bio-friendly elements, they are in line with the international development trend of "aluminum-free and vanadium-free" medical titanium alloys.

[0017] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description

[0018] Figure 1 The images show the morphology and particle size distribution of the titanium-molybdenum-zirconium pre-alloyed powder prepared in Example 1 of this invention; (a) is a microscopic morphology of the powder; (b) is a particle size distribution of the powder.

[0019] Figure 2 The images show microscopic tissue images of the dental restorations prepared in Example 1 of this invention; (a) is a tissue photograph before porcelain fusion; (b) is a tissue photograph after porcelain fusion.

[0020] Figure 3 This is a morphology diagram of the titanium-molybdenum-zirconium pre-alloyed powder prepared in Example 2 of the present invention.

[0021] Figure 4 This is a morphology diagram of the titanium-molybdenum-zirconium pre-alloyed powder prepared in Example 3 of the present invention.

[0022] Figure 5 Morphology diagram of TC4 powder provided for Comparative Example 1.

[0023] Figure 6 This is a morphology diagram of the Ti-15Zr powder prepared in Comparative Example 3 of this invention.

[0024] Figure 7 This is a microscopic tissue photograph of the dental restoration prepared in Example 4 of the present invention.

[0025] Figure 8 This is a microscopic tissue photograph of the dental restoration prepared in Example 5 of the present invention.

[0026] Figure 9 This is a microscopic tissue photograph of the dental restoration prepared in Example 6 of the present invention.

[0027] Figure 10 This is a microscopic photograph of the dental restoration prepared in Comparative Example 4 of the present invention.

[0028] Figure 11 This is a microscopic photograph of the dental restoration prepared in Comparative Example 5 of the present invention.

[0029] Figure 12 This is a microscopic photograph of the dental restoration prepared in Comparative Example 6 of the present invention. Detailed Implementation

[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0031] Ti-6Al-4V (TC4), with its excellent mechanical properties, has become one of the most widely used titanium alloys in dental restorations, used in porcelain-fused-to-metal (PFM) crown and bridge bases, removable partial denture frameworks, and implant superstructures. However, TC4 has gradually revealed two prominent problems in clinical applications. Firstly, TC4 contains aluminum (Al) and vanadium (V). Studies have shown that the release of vanadium from dental implants may raise concerns about biological effects. Although the release of Al / V is small, long-term exposure still poses risks of cellular and tissue toxicity, potentially leading to complications such as organ damage, osteomalacia, anemia, and neurological disorders. Therefore, developing aluminum- and vanadium-free β-type titanium alloys has become an important direction for the development of dental restorative materials. Secondly, when TC4 is used in porcelain-fused-to-metal (PFM) crowns and bridges, the gold-ceramic fit is difficult to meet the requirements for long-term clinical stability. Porcelain-fused-to-metal (PFM) restorations place strict requirements on the matching of the thermal expansion coefficients of the alloy and the porcelain powder, as well as the control of deformation after repeated baking. The thermal expansion coefficients of the alloy and the porcelain powder must be strictly matched; the alloy melting point must be 170-270℃ higher than the porcelain powder melting point; and the metal substrate must withstand multiple porcelain-baking cycles at 750-950℃ without deformation, oxide film peeling, or porcelain cracking. Research has found a mismatch in the thermal expansion coefficients between the TC4 substrate and the opaque porcelain. With increased baking cycles and temperatures, cracks approximately 0.5-1.0 μm wide often appear between the TC4 substrate and the oxide film, severely affecting the porcelain-metal bond strength. Further research indicates that compared to cobalt-chromium alloys, titanium-based alloys are more prone to a decrease in porcelain-metal bond strength after thermomechanical cycling, and the porcelain-metal bond strength of titanium-based alloys is affected by the metal processing techniques used. This represents a critical technical bottleneck that urgently needs to be addressed for the metal substrates of porcelain-fused-to-metal crowns and bridges used in premolars and load-bearing areas of the molar region.

[0032] Meanwhile, removable partial denture frameworks (especially those with clasps) place another dimension of performance requirements on materials: the clasp area needs to possess high elastic deformation capacity and appropriate strength matching to achieve clasp retention and withstand long-term fatigue from insertion and removal. TC4 has a high yield strength but relatively low elongation, making it insufficient in terms of resilience and plasticity reserve when used as a clasp material; while pure titanium, although biocompatible, has low strength, making it difficult to simultaneously meet the strength requirements of crown and bridge abutments. Therefore, there is an urgent clinical need for a new generation of dental titanium alloy materials that can serve a dual purpose, suitable for both porcelain-fused-to-metal crown and bridge abutments and removable frameworks with clasps, and free of Al and V elements.

[0033] Selective laser melting (SLM) technology provides an effective approach for the customized and precision manufacturing of dental restorations. SLM uses a laser beam as an energy source to scan and melt metal powder layer by layer according to the contour of a three-dimensional model slice. This allows for the direct forming of dental restorations with complex internal cavities, thin walls, and delicate clasp structures, significantly improving forming accuracy and material utilization compared to traditional casting processes. However, the forming quality of SLM technology is highly dependent on the properties of the metal powder. Currently, the titanium alloy powder used for SLM in China is mainly concentrated in the TC4 grade, whose inherent Al and V element problems and porcelain-ceramic matching defects still exist after SLM forming. Furthermore, for the specific conditions of dental restorations, Al / V-free Ti-Mo-Zr (Ti-Mo-Zr) pre-alloyed powders adapted to the SLM process have not yet formed a systematic technical solution in terms of powder composition design, particle size and shape control, oxygen, nitrogen, and hydrogen impurity management, and subsequent heat treatment processes. Existing research on Ti-Mo-Zr alloys mainly focuses on the field of bone implantation. Their design logic of "the lower the modulus, the better" is significantly different from the triple requirements of "strength-plasticity-ceramic cycle stability" for dental porcelain crowns and bridges and removable frameworks. At the same time, conventional Ti-Mo-Zr alloys often exhibit problems such as excessively high strength, insufficient elongation and performance dispersion after SLM forming, making it difficult to meet the performance threshold of restoration materials.

[0034] In light of the above background, there is an urgent need to develop a titanium-molybdenum-zirconium pre-alloy powder for SLM (Self-Made Plastic-Lift) that is free of Al and V elements and can simultaneously meet the requirements for use in porcelain crowns and bridges as well as removable brackets with clasps. This powder, through a reasonable Mo / Zr ratio and controlled impurity content, combined with an air-atomization powder preparation process and a corresponding heat treatment regime, can achieve a good match of strength, plasticity, and elastic modulus after SLM forming. Furthermore, it maintains stable microstructure and properties after multiple porcelain-fused-to-metal (PFM) thermal cycles, thus fundamentally solving the dual dilemmas faced by TC4 titanium alloys in dental restorations: concerns about the biocompatibility of Al and V and insufficient porcelain-fused-to-metal compatibility.

[0035] The present invention provides a titanium-molybdenum-zirconium pre-alloyed powder, the chemical composition of which, by mass percentage, includes: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%, with the balance being Ti and unavoidable impurities.

[0036] The titanium-molybdenum-zirconium pre-alloy powder provided in this application is a Ti-Mo-Zr alloy. Since Mo is a powerful β stabilizer in this titanium alloy, it can significantly reduce the elastic modulus of the titanium alloy and improve its corrosion resistance. Furthermore, since Zr belongs to the same group as Ti (IVB), it can improve the mechanical strength and biocompatibility of the titanium alloy. Moreover, Mo and Zr do not have cytotoxic reactions when in contact with cells. Therefore, the titanium-molybdenum-zirconium pre-alloy powder provided in this application has high toughness, low elastic modulus, and good biocompatibility even without toxic elements.

[0037] Meanwhile, the titanium-molybdenum-zirconium pre-alloyed powder provided in this application also controls the limits of impurities containing O, N, and H (O≤0.15wt%, N≤0.035wt%, H≤0.008wt%) to avoid impurities such as oxygen, nitrogen, and hydrogen, which are harmful interstitials in titanium alloys, from severely hardening the titanium matrix, significantly reducing plasticity and elongation, causing increased brittleness of SLM-printed parts, and performance fluctuations.

[0038] The titanium-molybdenum-zirconium pre-alloy powder provided in this application does not contain Al or V elements and can solve the following three key technical problems: First, it eliminates the biosafety hazards of Al and V elements; second, it enables the same material to meet both the strength and ceramic bonding requirements of the metal substrate of porcelain crowns and bridges, and the resilience and plasticity requirements of removable stents with clasps; third, it ensures that the restoration can maintain tissue and performance stability after multiple porcelain heating cycles, thereby overcoming the inherent defects of "one material cannot be used for two purposes" and "performance decay after porcelain heating cycles" in the existing technology.

[0039] In some possible embodiments, the titanium-molybdenum-zirconium pre-alloyed powder is an alloy powder prepared by aerosol method; the particle size distribution D10 of the titanium-molybdenum-zirconium pre-alloyed powder is 12μm~25μm, the particle size distribution D90 is 50μm~65μm, and the sphericity of the titanium-molybdenum-zirconium pre-alloyed powder is ≥0.85.

[0040] Here, the titanium-molybdenum-zirconium pre-alloyed powder is selected as an alloy powder prepared by the aerosol method. This enables the powder to achieve a good match of strength, plasticity and elastic modulus after SLM forming, and to maintain the stability of its structure and properties after multiple porcelain thermal cycles. This fundamentally solves the dual dilemma of Al and V biocompatibility concerns and insufficient porcelain matching faced by TC4 titanium alloy in dental restoration.

[0041] In this application, by selecting the particle size distribution D10 of the titanium-molybdenum-zirconium pre-alloyed powder to be 12μm~25μm, the fine powder content of the powder can be controlled. This avoids insufficient powder filling due to too low a fine powder content, and easy agglomeration and dust generation due to excessively small fine powder (<12μm), thus preventing splattering during SLM printing. By selecting the particle size distribution D90 of the titanium-molybdenum-zirconium pre-alloyed powder to be 50μm~65μm, the maximum particle size of the powder can be controlled. This avoids excessively large particle size (D90) resulting in too many large particles, limiting the thickness of the SLM powder layer, making it difficult to print delicate microstructures such as thin-walled dental structures, fine clasps, and crown bridge bases, which are prone to incomplete fusion defects. Conversely, excessively small particle size (D90) results in an overall fine powder, which also leads to oxygen absorption and splattering problems, making the printed parts prone to porosity.

[0042] As can be seen, the combination of D10 and D90 particle sizes here forms a particle size distribution with appropriate width and width, with large and small particles filling each other, which is suitable for the powder layer thickness commonly used in SLM equipment (generally 20-50μm), and takes into account both powder flowability and printing density.

[0043] Furthermore, the sphericity of the titanium-molybdenum-zirconium pre-alloyed powder is ≥0.85, which indicates the degree to which the powder particles approximate ideal spheres. The closer the value is to 1, the better the particle sphericity, and the lower the proportion of satellite powder, irregularly shaped powder, and broken powder. This avoids the irregular shape of the powder particles and poor flowability caused by a sphericity below 0.85, which can easily lead to bridging, uneven accumulation, and large fluctuations in the thickness of the powder layer during SLM powder spreading.

[0044] In some possible embodiments, the flowability of the titanium-molybdenum-zirconium pre-alloyed powder is ≤40s / 50g, and the loose pack density of the titanium-molybdenum-zirconium pre-alloyed powder is ≥2.8g / cm³. 3 .

[0045] By limiting the flowability of the titanium-molybdenum-zirconium pre-alloyed powder to ≤40s / 50g, issues such as powder bridging, arching, localized powder shortages, and uneven powder layer thickness that easily occur during powder spreading by the powder spreading roller or scraper in SLM equipment can be avoided. Furthermore, by limiting the loose packing density of the titanium-molybdenum-zirconium pre-alloyed powder to ≥2.8g / cm³, [further details can be provided]. 3 This avoids the situation where the gaps between powder particles are large and there are many pores inside the powder layer. As a result, when the powder is melted by the laser, the original pores of the powder bed are not difficult to completely eliminate, which leads to the problem of residual pore defects in the printed parts.

[0046] In some possible embodiments, after a single laser selective melting process, the oxygen content of the titanium-molybdenum-zirconium pre-alloyed powder increases by ≤100ppm and the sphericity is ≥0.80.

[0047] It should be noted that by simulating the working conditions of powder being irradiated by laser and subjected to high-temperature molten pool heat radiation during SLM printing, a laser selective melting treatment was performed on the titanium molybdenum zirconium pre-alloy powder to assess the degree of performance degradation of the titanium molybdenum zirconium pre-alloy powder after being subjected to laser heat, in order to simulate the state of recycled powder that was not melted during the printing process.

[0048] After a single laser selective melting (SLM) treatment, the oxygen content of the Ti-Mo-Zr pre-alloyed powder increased by ≤100ppm. This indicates that during SLM printing, some powder does not participate in component forming and is recycled due to laser thermal radiation and high-temperature baking in the molten pool. Titanium alloy powder has high chemical reactivity and readily adsorbs oxygen at high temperatures, leading to an increase in the oxygen content of the recycled powder. Therefore, limiting the oxygen increase to ≤100ppm indicates that the Ti-Mo-Zr pre-alloyed powder possesses excellent resistance to high-temperature oxygen absorption, and the oxygen content will not accumulate rapidly during the SLM thermal cycling recycling process.

[0049] After a single laser selective melting treatment, the sphericity of the titanium-molybdenum-zirconium pre-alloyed powder is ≥0.80, which can limit the degree of particle morphology deterioration after the powder is subjected to laser heat treatment and ensure that the recycled titanium-molybdenum-zirconium pre-alloyed powder still maintains a good particle morphology.

[0050] In some possible embodiments, the surface of the titanium-molybdenum-zirconium pre-alloyed powder particles is formed with an oxygen enrichment gradient layer with a thickness of 50 nm to 500 nm. The oxygen content in the oxygen enrichment gradient layer decreases from the surface to the interior of the particles. Specifically, the oxygen content at the surface of the oxygen enrichment gradient layer is ≥0.25 wt%, and the oxygen content at the core of the oxygen enrichment gradient layer is ≤0.10 wt%.

[0051] Here, the thickness of the oxygen enrichment gradient layer is 50nm~500nm. The oxygen content in the oxygen enrichment gradient layer decreases from the surface to the inside of the particles. Therefore, the oxygen content is highest on the outermost surface of the powder particles. The oxygen content gradually decreases along the radial direction of the particles. When the oxygen content reaches the inner boundary of the gradient layer (the core of the gradient layer), the oxygen content drops to ≤0.10wt%. Further inward is the powder particle matrix, which maintains the low oxygen level of the powder.

[0052] A second aspect of the present invention provides a method for preparing the titanium-molybdenum-zirconium pre-alloyed powder as described above, comprising the following steps: (1) Prepare the raw materials for titanium-molybdenum-zirconium pre-alloyed to prepare electrode rods using the prepared raw materials; (2) The electrode rod prepared in step (1) is powdered under the protection of high-purity argon gas by using the electrode induction melting gas atomization method to obtain titanium molybdenum zirconium pre-alloy powder.

[0053] In step (1), the raw materials are weighed and proportioned according to the following chemical composition by mass percentage: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%, with the balance being Ti and unavoidable impurities. The proportioned raw materials are then processed into electrode rods, which serve as the smelting raw materials for subsequent gas atomization. The electrode rods are the input billets for the electrode induction melting gas atomization process, and the uniformity of the rod composition directly determines the consistency of the final powder composition. It is necessary to ensure that the Mo and Zr alloying elements are fully dissolved in the rods to reduce component segregation; at the same time, the O, N, and H impurities in the raw materials themselves must be controlled to prevent interstitial impurities from the source.

[0054] In step (2), the electrode rod prepared in step (1) is powdered under the protection of high-purity argon gas using the electrode induction melting gas atomization method to obtain the titanium-molybdenum-zirconium pre-alloy powder. The electrode rod is melted without a crucible by the induction coil. The end of the rod is continuously melted to form a metal liquid flow. High-pressure high-purity argon gas impacts the metal liquid flow and breaks it into tiny droplets. The droplets are rapidly cooled and solidified in the argon atmosphere to obtain the pre-alloy powder.

[0055] Using the above method, by pre-mixing and forming rods, and then combining them with electrode induction melting, the Mo and Zr elements can be fully fused together. The resulting powder particles have good compositional consistency, which reduces the performance dispersion of SLM formed components and ensures "one material for two uses". At the same time, it can meet the performance requirements of porcelain crown bridge substrates and removable brackets with retaining rings.

[0056] In some possible embodiments, the process further includes: subjecting the formulation obtained in step (2) to controlled oxidation treatment for 1 to 4 hours at a temperature of 300°C to 500°C and an oxygen partial pressure of 0.001 atm to 0.1 atm, so that the surface layer of the formulation forms an oxygen-enriched gradient layer with a thickness of 50 nm to 500 nm, and controlling the overall oxygen content of the titanium-molybdenum-zirconium pre-alloy powder to 0.05 wt% to 0.20 wt%.

[0057] By constructing an oxygen-rich gradient layer of 50nm~500nm on the surface of the powder particles through controlled oxidation treatment, a unique structure of "low modulus β phase matrix (≤95GPa) + high modulus gradient surface region (≥110GPa)" is formed in the obtained repair body after SLM forming and two-step heat treatment. After the repair body is subjected to three simulated porcelain firing cycles at 850℃, the elongation of the repair body decreases by ≤6.6%, and the metal-ceramic bonding strength is ≥30MPa. It can be seen that this powder is superior to the uncontrolled oxidation-treated powder of the same composition and TC4.

[0058] A third aspect of the present invention provides a method for preparing a dental restoration, comprising the following steps: (1) Under the protection of an inert gas with an oxygen content of ≤0.1%, the above-mentioned titanium-molybdenum-zirconium pre-alloy powder is spread to form a powder layer with a thickness of 20μm~40μm. (2) The powder layer formed in step (1) is laser selective melting and forming to obtain the matrix by using preset process parameters; the preset process parameters are: laser power of 90W~250W, scanning speed of 500mm / s~1200mm / s, and scanning distance of 45μm~110μm. (3) Using a combination of checkerboard scanning and rotation scanning, the scanning direction of adjacent layers is rotated by 67° to form the substrate obtained in step (2) to obtain the shaped part; (4) The molded part obtained in step (3) is subjected to two heat treatments and polishing treatments in sequence to obtain a dental restoration; wherein, the first heat treatment of the molded part includes holding it at a heat treatment temperature of 760℃~790℃ for 20min~60min and then air cooling it to room temperature; the second heat treatment of the molded part includes holding it at a heat treatment temperature of 660℃~790℃ for 1h~2h and then air cooling it to room temperature.

[0059] Here, the prepared dental restorations completely eliminate the biocompatibility risks associated with Al and V elements. Furthermore, since Mo and Zr are both recognized bio-friendly elements, this aligns with the international trend towards "aluminum-free and vanadium-free" medical titanium alloys. Simultaneously, this preparation method achieves "dual-purpose use of one material." Through Mo and Zr compositional window design and two-step heat treatment (760℃~790℃ and air cooling + 660℃~790℃ and air cooling), the SLM-formed restorations achieve a yield strength of 780MPa~950MPa and an elongation at break of ≥8%, meeting the performance requirements of porcelain-fused-to-metal crown and bridge bases (ISO 22674 Type 4) and removable partial prosthesis frameworks (ISO 22674 Type 5).

[0060] The fourth aspect of the present invention provides a dental prosthesis, which is prepared by the above-described method for preparing dental prostheses. The prosthesis is a porcelain crown bridge with a metal base or a removable partial denture framework with clasps.

[0061] In some possible embodiments, the relative density of the dental restoration is ≥99.5%, the microstructure is a β-phase matrix with diffusely distributed α-precipitates, and the volume fraction of the β-phase is ≥70%; the specified non-proportional elongation strength Rp0.2 of the dental restoration is 780MPa~950MPa, the elongation after fracture is ≥8%, and the elastic modulus is ≤105GPa; after three simulated porcelain-fused-to-metal cycles at 850℃, the Rp0.2 of the dental restoration remains at 780MPa~950MPa, the decrease in elongation after fracture is ≤20%, and the metal-ceramic bond strength is ≥30MPa.

[0062] The following examples illustrate a method for preparing a dental restoration according to the present invention. It should be noted that, unless otherwise specified, the methods, reagents, and materials described in the following examples are all commercially available; and the experimental methods described are conventional methods unless otherwise specified.

[0063] Example 1 A method for preparing a dental restoration includes the following steps: Step 1: Powder Preparation. Weigh 16% Mo, 6% Zr, and the balance Ti (all with purity ≥99.9%) by mass percentage and prepare electrode rods via vacuum arc melting. Powdering is then performed on the electrode rods using a vacuum atomization method under high-purity argon gas (purity ≥99.999%) protection at an atomization pressure of 5.0 MPa. The collected powder is sieved to obtain titanium-molybdenum-zirconium pre-alloy powder with D10=20.1 μm and D90=64.3 μm. Testing revealed an oxygen content of 104 ppm (0.0104 wt%), a nitrogen content of 296 ppm (0.0296 wt%), a hydrogen content of 14 ppm (0.0014 wt%), a sphericity of 90%, a flowability of 35 s / 50 g, and a loose packing density of 2.88 g / cm³. 3 The tap density is 3.38 g / cm³. 3 After one SLM cycle, the oxygen content of the powder increased to 113 ppm (an increase of 9 ppm), while the sphericity remained at 90%, still meeting the molding requirements.

[0064] Step 2: SLM forming. The titanium-molybdenum-zirconium pre-alloy powder obtained in Step 1 was spread into a 30 μm layer under a high-purity argon atmosphere with an oxygen content ≤0.1%. The laser selective melting forming parameters were: laser power 180 W, scanning speed 800 mm / s, scanning spacing 100 μm, spot diameter 100 μm, and volumetric energy density 75 J / mm³. A checkerboard scanning strategy was used, with the scanning direction of adjacent layers rotated by 67° to obtain the formed parts, which included tensile and bending specimens.

[0065] Step 3: Two-step heat treatment. The molded part is taken out along with the substrate and subjected to two-step heat treatment in a vacuum furnace (vacuum degree ≤10⁻³ Pa): The first step is to hold at 780℃ for 30 minutes, then fill with high-purity argon gas and turn on the fan to force cooling to room temperature (air cooling); the second step is to hold at 700℃ for 1 hour, then air cool to room temperature. After polishing, the dental restoration is obtained.

[0066] The dental restoration obtained in Example 1 was subjected to performance testing. The relative density of this restoration was 99.6% (Archimedes displacement method). Figure 1As shown, microscopic observation of the dental restoration revealed a diffusely distributed nanoscale α-precipitate phase within a β-phase matrix, with a β-phase volume fraction of approximately 75%. Furthermore, the mechanical properties of the dental restoration were tested as follows: 0.2% specified non-proportional elongation strength Rp0.2 was 822 MPa, tensile strength Rm was 906 MPa, elongation after fracture A was 8.7%, flexural strength was 2070 MPa, and the flexural modulus in the unannealed state was 75.7 GPa.

[0067] Simulated porcelain-fused-to-metal (PFM) cycles were performed on dental restorations. The restorations were placed in a muffle furnace and subjected to three simulated PFM cycles according to the dental PFM process: heating to 850℃ (heating rate 50℃ / min), holding at that temperature for 5 minutes, and then cooling to room temperature with the furnace. Mechanical properties were tested after the cycles: Rp0.2 was 815 MPa, elongation after fracture was 8.2%, and the decrease was 5.7%. Figure 2 As shown, metallographic observation revealed that the proportion of the β phase in the dental restoration remained essentially unchanged, with no obvious cracks or interfacial delamination observed. The metal-ceramic bond strength was tested according to ISO 9693-1 standard, and the result was 32 MPa.

[0068] Example 2 The preparation method of the dental restoration provided in Example 2 is basically the same as that in Example 1, except that the Mo content is adjusted to 15% and the Zr content to 5%, while the remaining components, powder preparation, SLM process, and heat treatment are the same. The morphology of the titanium-molybdenum-zirconium pre-alloy powder prepared in Example 2 is as follows: Figure 3 As shown. The obtained powder had an oxygen content of 120 ppm, a sphericity of 91%, and a flowability of 35 s / 50 g. After SLM forming, it underwent a two-step heat treatment (780℃×30 min air cooling + 700℃×1 h air cooling). The mechanical properties were: Rp0.2=795MPa, Rm=870MPa, A=9.1%, and flexural strength 1980MPa. After 3 simulated ceramic firing cycles, Rp0.2=788MPa and A=8.5%, a decrease of 6.6%.

[0069] Example 3 The preparation method of the dental restoration provided in Example 3 is basically the same as that in Example 1, except that the Mo content is adjusted to 17% and the Zr content is adjusted to 7%, while the other conditions remain the same. The morphology of the titanium-molybdenum-zirconium pre-alloy powder prepared in Example 3 is as follows: Figure 3As shown. The obtained powder had an oxygen content of 98 ppm, a sphericity of 91%, and a flowability of 35 s / 50g. After SLM forming, it underwent a two-step heat treatment (780℃×30min air cooling + 700℃×1h air cooling). The mechanical properties were: Rp0.2=845MPa, Rm=920MPa, A=8.0%, and flexural strength 2120MPa. After 3 simulated ceramic firing cycles, Rp0.2=832MPa and A=7.6%, a decrease of 5.0%.

[0070] Comparative Example 1 Commercially available TC4 (Ti-6Al-4V) was used to atomize spherical powder (D10=20μm, D90=63μm, sphericity ≥0.85). The morphology of the TC4 powder corresponding to Comparative Example 1 is as follows: Figure 5 As shown; formed under the same SLM process parameters, followed by conventional annealing according to TC4 (850℃ × 1h furnace cooling). Mechanical properties: Rp0.2 = 1066 MPa, A = 10.6%, flexural modulus approximately 110 GPa. After 3 simulated ceramic firing cycles, metallographic observation revealed microcracks approximately 0.5 μm wide at the metal-ceramic interface, and the ceramic bond strength test value was 18 MPa, lower than the 32 MPa of Example 1.

[0071] Comparative Example 2 The same Ti-16Mo-6Zr powder and SLM process as in Example 1 were used, but the heat treatment was changed to a single step: 550℃ × 4h air cooling (simulating medium-temperature aging in existing technology). Mechanical properties: Rp0.2 = 1108MPa, A = 4.4%, flexural strength 2046MPa. It is evident that the strength is too high and the elongation is insufficient, failing to meet the plasticity (≥8%) requirement for the retainer. After 3 simulated ceramic firing cycles, A dropped to 2.1%, indicating severe performance degradation.

[0072] Comparative Example 3 Referring to the patent technology in CN117020230B, using Ti-15Zr pre-alloyed powder (D10=18μm, D90=60μm), the morphology of the Ti-15Zr powder prepared in Comparative Example 3 is shown in the figure below. Figure 6 As shown; the SLM parameters are consistent with those of this embodiment, and the heat treatment is water quenching at 800℃ for 30 minutes. Mechanical properties: Rp0.2 = 1015 MPa, A = 10.6%, flexural modulus approximately 95 GPa. After 3 simulated ceramic coating cycles, Rp0.2 = 990 MPa, A = 9.8%, but this alloy does not contain Mo, resulting in a high elastic modulus (approximately 95 GPa). Furthermore, the absence of Mo in the composition prevents the achievement of the comprehensive effect of stabilizing the β phase, reducing the modulus, and improving ceramic coating matching as described in this invention.

[0073] Table 1 shows a comparison of the key performance characteristics of Examples 1 to 3 and Comparative Examples 1 to 3.

[0074] Table 1. Comparison of key performance of Examples 1 to 3 and Comparative Examples 1 to 3

[0075] As shown in Table 1, after two-step heat treatment, the yield strength of Examples 1-3 of this invention is controlled within the range of 780-950 MPa, and the elongation after fracture is ≥8%, achieving a good match between strength and plasticity, meeting the requirements of Type 5 (clamp material) in ISO 22674 (Rp0.2≥500MPa, A≥2%). More importantly, after three simulated porcelain-fused-to-metal cycles, the elongation decrease is ≤6.6%, far superior to Comparative Example 2 (decreased by 52.3%), and the porcelain bond strength is ≥26 MPa, superior to the 18 MPa of Comparative Example TC4. This indicates that this invention, through the synergistic design of composition window, powder structure characteristics, SLM process, and two-step heat treatment, successfully solves the core technical problems of "difficulty in using one material for two purposes" and "performance degradation after porcelain-fused-to-metal cycles" in existing Al / V-free titanium alloys for dental restorations.

[0076] Therefore, this application achieves significant technical results through the synergistic design of composition windows, detectable powder structural features, SLM process parameters, and a two-step heat treatment regime. First, the titanium-molybdenum-zirconium pre-alloy powder provided by this invention is free of Al and V elements, completely eliminating the potential biosafety hazards of Al and V elements in traditional titanium alloys such as TC4. This aligns with the international trend of "aluminum-free and vanadium-free" medical titanium alloys, providing a safer material option for dental restorations. Second, through the composition window design of 12-20% Mo and 4-10% Zr, combined with a two-step heat treatment (760-790℃ air cooling + 660-700℃ air cooling), the restoration formed by SLM achieves a yield strength of 780-950 MPa and an elongation at break of ≥8%, demonstrating excellent strength-plasticity matching. This performance range precisely covers the strength requirements of the metal substrate for porcelain-fused-to-metal crowns and bridges (ISO 22674 Type 4: Rp0.2≥360MPa) and the resilience and plasticity requirements of removable scaffolds with clasps (ISO 22674 Type 5: Rp0.2≥500MPa, A≥2%), while allowing sufficient margin, achieving the clinical goal of using a single material to accommodate two types of restorations. Furthermore, after three cycles of simulated porcelain-fused-to-metal fusion at 850℃, the post-fracture elongation of the restoration of this invention decreased by ≤6.6%, far superior to the 52.3% decrease in Comparative Example 2 (single-step heat treatment); the metal-ceramic bonding strength was ≥30MPa, superior to the 18MPa of Comparative Example 4 (TC4). This indicates that the microstructure of the β-phase matrix + dispersed α-precipitated phase obtained by the two-step heat treatment of this invention maintains good phase stability and interfacial bonding during repeated high-temperature porcelain-fused-to-metal fusion, effectively solving the common problems of porcelain chipping and peeling in existing titanium alloy porcelain-fused-to-metal restorations. Furthermore, after one SLM cycle, the oxygen content of the powder of this invention increases only slightly, the sphericity remains above 90%, and the flowability is still ≤38 s / 50g, indicating that the powder has good recyclability and helps reduce production costs and material waste. The elastic modulus of the restoration of this invention is ≤105GPa (the flexural modulus in the unannealed state is about 75.7GPa), which is lower than TC4 (about 110GPa), which helps to reduce stress concentration between the crown and bridge framework and the opposing tooth or abutment tooth, and improves the long-term mechanical fit of the restoration. Compared with the single-step heat treatment scheme of existing Ti-Mo-Zr alloys (Comparative Example 2), the two-step heat treatment of the present invention reduces the yield strength from 1100+MPa to the 800-950MPa range, while increasing the elongation from 1-6% to ≥8%, solving the pain point of "excessive strength but insufficient plasticity" in the prior art; compared with TC4, the present invention eliminates Al and V elements and improves porcelain matching while maintaining sufficient strength; compared with Ti-15Zr dental alloy (Comparative Example 3), the present invention obtains a lower elastic modulus and better porcelain cycling stability by adding Mo.

[0077] Example 4 A method for preparing a dental restoration includes the following steps: Step 1: Preparation of Titanium-Molybdenum-Zirconium Pre-alloyed Powder: Mo 16%, Zr 6%, and the balance Ti (purity ≥99.9%) were weighed by mass percentage and formed into electrode rods by vacuum arc melting. Pre-alloyed spherical powder was obtained by electrode induction melting and vacuum atomization under high-purity argon gas (purity ≥99.999%) protection at an atomization pressure of 5.0 MPa. The obtained powder was placed in a tube furnace and subjected to controlled oxidation treatment at 400℃ and an oxygen partial pressure of 0.01 atm for 2.5 h, forming an oxygen-enriched gradient layer with a thickness of approximately 200 nm on the powder surface, thus obtaining the titanium-molybdenum-zirconium pre-alloyed powder. Testing showed that the overall oxygen content of the powder was 0.12 wt% (1200 ppm), the surface oxygen content was 0.32 wt%, and the core oxygen content was 0.09 wt%; the nitrogen content was 280 ppm (0.028 wt%), and the hydrogen content was 60 ppm (0.006 wt%). After sieving, the powder has a particle size distribution of D10=18.5μm, D90=58.2μm, sphericity of 91%, flowability of 35s / 50g, and loose density of 2.92g / cm³. 3 .

[0078] Step 2, SLM Forming: Powder spreading is performed under the protection of high-purity argon gas with an oxygen content ≤0.1%, with a layer thickness of 30μm. The laser selective melting forming parameters are: laser power 200W, scanning speed 800 mm / s, scanning spacing 80μm, spot diameter 100μm, and volumetric energy density approximately 83J / mm². 3 A checkerboard scanning strategy is adopted, with the scanning direction of adjacent layers rotated by 67° to obtain shaped parts. The shaped parts are tensile specimens (refer to GB / T 228.1-2010) and bending specimens (refer to GB / T 232-2010).

[0079] Step 3, Two-step heat treatment: Remove the molded part along with the substrate and heat it in a vacuum furnace (vacuum degree ≤10). -3 The process involves two heat treatment steps: the first step is to hold the temperature at 780℃ for 30 minutes, followed by filling with high-purity argon gas and turning on the fan to force cooling to room temperature (air cooling); the second step is to hold the temperature at 700℃ for 1 hour, followed by air cooling to room temperature. After polishing, the final dental restoration is obtained.

[0080] After the above heat treatment, the relative density of the dental restoration is 99.7% (Archimedes' displacement method). See also Figure 7Microstructural observation revealed that the dental restoration matrix consisted of a β-phase matrix with diffusely distributed nanoscale α-precipitates, comprising approximately 75% by volume. A high-modulus gradient zone with a depth of approximately 50 μm was formed at the original surface location of the particles. Nanoindentation testing showed that the matrix elastic modulus was 82 GPa, and the elastic modulus of the high-modulus gradient zone was 115 GPa. Mechanical properties: 0.2% specified non-proportional elongation strength Rp0.2 was 835 MPa, tensile strength Rm was 912 MPa, elongation after fracture A was 9.2%, and flexural strength was 2100 MPa.

[0081] The dental restoration was placed in a muffle furnace and subjected to three simulated porcelain-fused-to-metal (PFM) cycles according to the dental porcelain-fused-to-metal process: heating to 850℃ (heating rate 50℃ / min), holding for 5 minutes, and then cooling to room temperature with the furnace. After the cycles, mechanical properties were tested: Rp0.2 was 828 MPa, elongation after fracture was 8.8%, a decrease of 4.3%; metallographic observation showed that the gradient microstructure remained intact, with no obvious cracks or interface delamination. The metal-ceramic bond strength was tested according to ISO 9693-1 standard, and the result was 35 MPa.

[0082] Example 5 The preparation method of the dental restoration provided in Example 5 is basically the same as that in Example 4, except that the Mo content is adjusted to 15%, the Zr content is adjusted to 5%, and the controlled oxidation treatment temperature is 350℃ for 3 hours. The resulting powder has an overall oxygen content of 0.10wt%, a surface oxygen content of 0.28wt%, and a core oxygen content of 0.07wt%. The SLM forming and heat treatment parameters are the same as in Example 4; the microstructure of the dental restoration prepared in Example 5 is as follows. Figure 8 As shown. Mechanical properties: Rp0.2 = 805 MPa, A = 9.6%, flexural strength 1950 MPa. After 3 simulated ceramic bonding cycles, Rp0.2 = 798 MPa, A = 9.1%, a decrease of 5.2%, and the metal-ceramic bond strength 34 MPa.

[0083] Example 6 The preparation method of the dental restoration provided in Example 6 is basically the same as that in Example 4, except that the Mo content is adjusted to 18%, the Zr content is adjusted to 8%, and the controlled oxidation treatment temperature is 450℃ for 2 hours. The resulting powder has an overall oxygen content of 0.15wt%, a surface oxygen content of 0.36wt%, and a core oxygen content of 0.10wt%. The microstructure of the dental restoration prepared in Example 6 is as follows: Figure 9As shown. Mechanical properties: Rp0.2 = 860 MPa, A = 8.3%, flexural strength 2180 MPa. After 3 simulated ceramic bonding cycles, Rp0.2 = 852 MPa, A = 7.9%, a decrease of 4.8%, and the metal-ceramic bond strength 35 MPa.

[0084] Comparative Example 4 (Uncontrolled oxidation treatment) Ti-16Mo-6Zr pre-alloyed powder with the same composition as in Example 4 was used, but without controlled oxidation pretreatment; it was directly subjected to SLM forming and two-step heat treatment. The overall oxygen content of the powder was 0.012wt% (120ppm). The SLM forming and heat treatment parameters were the same as in Example 4. Mechanical properties: Rp0.2 = 825MPa, A = 8.8%, flexural strength 2050MPa. After 3 simulated ceramic bonding cycles, Rp0.2 = 808MPa, A = 7.1%, a decrease of 19.3%, and ceramic bond strength 31MPa. See also Figure 10 Microscopic observation revealed that the uncontrolled oxidation treatment resulted in uneven oxide film thickness on the surface of the restoration after porcelain fusion cycles, with localized microcracks and significantly lower gold-ceramic bonding strength compared to Example 4.

[0085] Comparative Example 5 (TC4 control group) Commercially available TC4 (Ti-6Al-4V) gas-atomized spherical powder (D10=20μm, D90=63μm, sphericity ≥0.85) was used for forming under the same SLM process parameters, followed by conventional TC4 annealing (850℃×1h furnace cooling). Mechanical properties: Rp0.2=1066MPa, A=10.6%, elastic modulus approximately 110GPa. After 3 simulated ceramic firing cycles, see [reference needed]. Figure 11 Metallographic observation revealed microcracks with a width of about 0.5 μm at the metal-ceramic interface, and the metal-ceramic bonding strength test value was 22 MPa, which is much lower than the 35 MPa in Example 4.

[0086] Comparative Example 6 (Uniform Oxygen Control) The same Ti-16Mo-6Zr pre-alloyed powder as in Example 4 was used, but the oxygen content was uniformly distributed to 0.12wt% (without a surface oxygen-enriched gradient layer) through overall oxygen infiltration treatment, followed by SLM forming and two-step heat treatment. Mechanical properties: Rp0.2 = 830MPa, A = 8.5%, flexural strength 2060MPa. After 3 simulated ceramic bonding cycles, Rp0.2 = 818MPa, A = 7.8%, a decrease of 8.2%, and ceramic bond strength 33MPa. See also Figure 12 Microscopic observation revealed that the overall uniformly oxygenated restoration had a relatively uniform oxide film thickness on the surface after ceramic calendering cycles, but lacked support from a high modulus gradient region. The gold-ceramic bonding strength was between that of Comparative Example 4 and Example 4.

[0087] Table 2 shows a comparison of the key performance characteristics of Examples 4 to 6 and Comparative Examples 4 to 6.

[0088] Table 2 Comparison of key performance of Examples 4 to 6 and Comparative Examples 4 to 6

[0089] As shown in Table 2, Examples 4-6 of this invention construct an oxygen-enriched gradient layer on the surface of powder particles through controlled oxidation pretreatment. After SLM forming and two-step heat treatment, a unique structure of "low-modulus β-phase matrix + high-modulus gradient surface layer" is formed in the repair body. Compared with Comparative Example 4 without controlled oxidation treatment, the elongation after porcelain fusion cycling in Example 4 decreased by only 4.3% (comparative Example 4 was 19.3%), and the porcelain bond strength increased by 45%. Compared with Comparative Example 6 with overall uniform oxygen control, Example 4 showed significantly better performance retention and porcelain bond strength after porcelain fusion cycling. Compared with Comparative Example 5 (TC4), this invention eliminates Al and V elements, and the porcelain bond strength is increased by 78%. This indicates that this invention successfully solves the core technical problems of "difficulty in using one material for two purposes," "uncontrollable surface oxygen distribution," and "performance degradation after porcelain fusion cycling" in the prior art through the synergistic design of constructing an oxygen-enriched gradient layer on the surface of powder particles and SLM process and two-step heat treatment.

[0090] This invention achieves the following technical effects through the synergistic design of constructing an oxygen-enriched gradient layer on the surface of powder particles and the SLM process and two-step heat treatment: First, it completely eliminates the biosafety hazards of Al and V elements. The controlled titanium dioxide molybdenum-zirconium pre-alloy powder provided by this invention does not contain Al or V elements, and Mo and Zr are both recognized bio-friendly elements, which is in line with the international development trend of "aluminum-free and vanadium-free" medical titanium alloys. Second, it achieves "dual-purpose material". Through the composition window design of 12-20% Mo and 4-10% Zr and two-step heat treatment (760-790℃ air cooling + 660-700℃ air cooling), the restoration formed by SLM obtains a yield strength of 780-950MPa and an elongation at break of ≥8%, while meeting the performance requirements of porcelain crown and bridge metal base (ISO 22674 Type 4) and removable partial denture framework (ISO 22674 Type 5). Third, controlled oxidation pretreatment constructs a 50-500 nm oxygen-enriched gradient layer on the surface of the powder particles. After SLM forming and two-step heat treatment, a unique structure of "low-modulus β-phase matrix (≤95GPa) + high-modulus gradient surface region (≥110GPa)" is formed within the repair body. After three simulated ceramic firing cycles at 850℃, the elongation decrease is ≤6.6%, and the metal-ceramic bonding strength is ≥30MPa, significantly better than untreated powder of the same composition and TC4. Fourth, after one SLM cycle, the oxygen content of the powder increases only slightly, and the sphericity remains ≥0.90, demonstrating good cyclic reuse stability and helping to reduce production costs.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A titanium-molybdenum-zirconium pre-alloyed powder, characterized in that, Its chemical composition by mass percentage includes: Mo: 12%~20%, Zr: 4%~10%, O: ≤0.15wt%, N: ≤0.035wt%, H: ≤0.008wt%, with the balance being Ti and unavoidable impurities.

2. The titanium-molybdenum-zirconium pre-alloyed powder according to claim 1, characterized in that, The titanium-molybdenum-zirconium pre-alloy powder is an alloy powder prepared by aerosol method; the particle size distribution D10 of the titanium-molybdenum-zirconium pre-alloy powder is 12μm~25μm, the particle size distribution D90 is 50μm~65μm, and the sphericity of the titanium-molybdenum-zirconium pre-alloy powder is ≥0.

85.

3. The titanium-molybdenum-zirconium pre-alloyed powder according to claim 1, characterized in that, The flowability of the titanium-molybdenum-zirconium pre-alloyed powder is ≤40s / 50g, and the loose pack density of the titanium-molybdenum-zirconium pre-alloyed powder is ≥2.8g / cm³. 3 .

4. The titanium-molybdenum-zirconium pre-alloyed powder according to claim 1, characterized in that, After one laser selective melting treatment, the oxygen content of the titanium-molybdenum-zirconium pre-alloyed powder increases by ≤100ppm and the sphericity is ≥0.

80.

5. The titanium-molybdenum-zirconium pre-alloyed powder according to claim 1, characterized in that, The titanium-molybdenum-zirconium pre-alloyed powder has an oxygen enrichment gradient layer with a thickness of 50 nm to 500 nm on the particle surface. The oxygen content in the oxygen enrichment gradient layer decreases from the surface to the interior of the particle. The oxygen content at the surface of the oxygen enrichment gradient layer is ≥0.25 wt%, and the oxygen content at the core of the oxygen enrichment gradient layer is ≤0.10 wt%.

6. A method for preparing titanium-molybdenum-zirconium pre-alloyed powder as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Prepare the raw materials for titanium-molybdenum-zirconium pre-alloyed to prepare electrode rods using the prepared raw materials; (2) The electrode rod prepared in step (1) is powdered under the protection of high-purity argon gas by using the electrode induction melting gas atomization method to obtain the titanium-molybdenum-zirconium pre-alloy powder.

7. The method for preparing titanium-molybdenum-zirconium pre-alloyed powder according to claim 6, characterized in that, Also includes: The formulation obtained in step (2) is subjected to controlled oxidation treatment for 1 to 4 hours at a temperature of 300℃ to 500℃ and an oxygen partial pressure of 0.001 atm to 0.1 atm, so that an oxygen-enriched gradient layer with a thickness of 50 nm to 500 nm is formed on the surface of the formulation, and the overall oxygen content of the titanium-molybdenum-zirconium pre-alloy powder is controlled at 0.05 wt% to 0.20 wt%.

8. A method for preparing a dental restoration, characterized in that, Includes the following steps: (1) Under the protection of an inert gas with an oxygen content ≤0.1%, the titanium-molybdenum-zirconium pre-alloy powder according to any one of claims 1 to 6 is spread to form a powder layer with a thickness of 20 μm to 40 μm. (2) The powder layer formed in step (1) is laser selective melting and forming to obtain a matrix by using preset process parameters; the preset process parameters are: laser power of 90W~250W, scanning speed of 500mm / s~1200mm / s, and scanning distance of 45μm~110μm. (3) Using a combination of checkerboard scanning and rotation scanning, the scanning direction of adjacent layers is rotated by 67° to form the substrate obtained in step (2) to obtain a shaped part; (4) The molded part obtained in step (3) is subjected to two heat treatments and polishing treatments in sequence to obtain the dental restoration; wherein, the first heat treatment of the molded part includes holding it at a heat treatment temperature of 760℃~790℃ for 20min~60min and then air cooling it to room temperature; the second heat treatment of the molded part includes holding it at a heat treatment temperature of 660℃~790℃ for 1h~2h and then air cooling it to room temperature.

9. A dental restoration, characterized in that, The dental restoration is prepared by the method described in claim 8, wherein the restoration is a porcelain crown / bridge with a metal base or a removable partial prosthesis framework with clasps.

10. The dental restoration according to claim 9, characterized in that, The relative density of the dental restoration is ≥99.5%, and the microstructure consists of a β-phase matrix with diffusely distributed α-precipitates and a β-phase volume fraction ≥70%. The specified non-proportional elongation strength Rp0.2 of the dental restoration is 780MPa~950MPa, the elongation after fracture is ≥8%, and the elastic modulus is ≤105GPa. After three cycles of simulated porcelain fusion at 850℃, the Rp0.2 of the dental restoration remains at 780MPa~950MPa, the decrease in elongation after fracture is ≤20%, and the metal-ceramic bond strength is ≥30MPa.

Citation Information

Patent Citations

  • A heat treatment process for a dental Ti-Zr alloy additively manufactured piece

    CN117020230B